With love, from Cold World - Thompson, Alicia, 1984- (Berkley Romance, 2023)
"She has a to-do list a mile long and falling for her coworker isn't on it-yet somehow he's become her top priority in this romantic comedy from the author of Love in the Time of Serial Killers. Lauren Fox is the bookkeeper for Cold World, a tourist destination that's always a winter wonderland despite being located in humid Orlando, Florida. Sure, it's ranked way below any of the trademarked amusement parks and maybe foot traffic could be better. But it's a fun place to work, even if "fun" isn't exactly Lauren's middle name. Her coworker Asa Williamson, on the other hand, is all about finding ways to enliven his days at Cold World-whether that means organizing the Secret Santa or teasing Lauren. When the owner asks Lauren and Asa to propose something (anything, really) to raise more revenue, their rivalry heats up as they compete to come up with the best idea. But the situation is more dire than they thought, and it might take these polar opposites working together to save the day. If Asa thought Lauren didn't know how to enjoy herself, he's surprised by how much he enjoys spending time together. And if Lauren thought Asa wasn't serious about anything, she's surprised by how seriously he seems to take her. As Lauren and Asa work to save their beloved wintery spot, they realize the real attraction might be the heat generating between them"--